Psychometric Properties of the Teachers’ Knowledge and Practice Scale for Students with ADHD - Carrillo Sierra, Sandra Milena; Silva Monsalve, Gloria; Cabrera Gómez, Claudia Carolina; Gutiérrez Suárez, Carlos; Rincón Rodriguez, Nayareth; Rivera Porras, Diego (Revista Criterios, 2023)
The psychometric properties of the scale of knowledge and pedagogical practice of teachers against inattention, hyperactivity, and impulsive behavior in school contexts in Cúcuta, Norte de Santander are validated. It was carried out under a quantitative, non-experimental approach, of exploratory, cross-sectional type, in terms of the population to be taken into account, who were the teachers assigned to the Municipal Education Secretary; the sample was obtained by proportional fixing; the data were processed in SPSS applying exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) based on reliability and reproducibility Cronbach’s alpha, test-retest with Lin’s intraclass correlation coefficient and the kappa index Cohen’s. It is concluded that the test has the appropriate psychometric properties for use in Colombian school contexts.